(untitled) (Revista da Tulha, 2015)
This lecture addresses the relationship and differences between the present musical practices in the suburbs of Sao Paulo, particularly in Cidade Tiradentes district, most popular housing complex in Latin America, with over 300 thousand inhabitants. From an ethnographic perspective, the research approaches the rap, like practiced in the neighborhood in the 1990s, and the funk style, especially its modality “Ostentation” whose music “won popularity” among residents of the periphery and beyond.